Illuminating the mechanisms to mitigate forced and child labour risks within Marine Stewardship Council certified fisheries. (September 2022) - Tindall, Charlotte; Oloruntuyi, Oluyemisi; Lees, Samantha; Longo, Catherine S.; Schley, David; Currey, Rohan J.C.
Abstract: Growing concern about forced and child labour abuses in the fishing industry has led to calls to integrate social issues within the sustainable seafood sector. While abusive labour practices in fisheries are increasingly studied, and consensus is building on overarching principles and benchmarks, few studies have reviewed the practical mechanisms available to mitigate forced and child labour risks. This paper provides an overview of labour risk management practices reported by fisheries certified to the Marine Stewardship Council (MSC) Fisheries Standard, representing over 15% of the world's marine capture fishery production. MSC-certified fisheries have been required to submit forced and child labour statements since 2018. The statements were analysed to examine the mechanisms to mitigate forced and child labour across different fishery contexts. Results indicated where MSC-certified vessels were broadly in line with expectations from international, private, and NGO standards or guidelines on labour issues, but also illustrated where there were departures. These could be explained by differences in how policy and practice are applied in different regulatory and cultural contexts, such as the requirement for use of written contracts in countries that have ratified ILO C188 versus the preference in some cases for the use of verbal share agreements. This reflects the challenge of creating culturally-appropriate, adaptable standards that are able to detect real risks of labour violations. To fully consider these nuances, our proposed framework captures key aspects of setting, implementing, and monitoring and enforcement of requirements alongside the roles of government, companies, and civil society. We propose this framework could be applied more broadly to evaluate fisheries' practices.